Effects of shot peening on the fatigue performance of ultrafine-grained CuNi3Si1Mg. (2nd September 2017) - Gholami, M.; Altenberger, I.; Kuhn, H.-A.; Wollmann, M.; Wagner, L.
ABSTRACT: This study evaluated the effects of shot peening (SP) for modifying the fatigue performance of ultrafine-grained CuNi3Si1Mg. Fatigue damage is possibly caused when electromechanical connectors are subjected to cyclic loading or high numbers of repeated plugging. The fatigue performance of the precipitation-hardened ultrafine-grained CuNi3Si1Mg was significantly enhanced from 325 MPa in the electropolished condition to 400 MPa after SP at an Almen intensity of 0.25 mmA. In the precipitation-hardened ultrafine-grained CuNi3Si1Mg, SP induced a high degree of work hardening and maximum compressive residual stress values on the surface layers, which resulted in a better fatigue performance than the electropolished counterpart. After SP, the dissolution of precipitates in the surface layers also improved fatigue performance by reduction in the negative effect of the surface precipitates.